PENGARUH SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA PENGADILAN DIMASA WABAH COVID-19 - Annisa Mulia Aghsya; Ratna Septiyanti; Yenni Agustina; Usep Syaipudin (Jurnal Akuntansi dan Keuangan (JAK), 2021)
This research aims to know the effect of management control system towards organizational performance in Pengadilan Negeri Tanjung Karang class IA during covid-19. This research is a quantitative study using a survey method with data collection techniques using a questionnaire which is measured by using the SPSS version 26 program. The population in this study were all employees of Pengadilan Negeri Tanjung Karang class IA, sampling using saturated sampling techniques namely all employees of Pengadilan Negeri Tanjung Karang class IA so that a total sample of 100 was obtained. The data analysis technique used the correlation test. The results of this study indicate that the management control system has a positive and significant effect on organizational performance during the Covid-19. With a determination coefficient of 0.728, the influence of management control system towards the performance of Pengadilan Negeri Tanjung Karang class IA during the Covid-19 was 72.8%, while the remaining 27.2% was influenced by other factors not examined in this study.